The Concepts of Health and Illness of Children Living with HIV in Jakarta, Indonesia: Implications for Future Programs - Thomas, Catherine; Irwanto; Weny Savitry Sembiring; Hana Panggabean; Rustono Farady Marta (Jurnal Online Psikogenesis, 2024)
Studies on children’s concepts of health and illness mostly took focus on the views of healthy children. As children living with HIV face different challenges, it is essential to gain more understanding on their views on health and illness. The study used a guided drawing activity followed by a semi-structured interview. Thematic coding was done to analyze of the interview data. There were three categories formed both on the concepts of health and illness: The biomedical, psychosocial, and healthy lifestyle representation. To children living with HIV, the concepts hospitals, hospitalization, medications, doctors, and symptoms of being sick are common to them. Children revealed the emotional fatigue from being regularly sick and hospitalized, being discriminated and having to pay medical bills as consequence of having poor health. On the other hand, children also acknowledged the positive consequences of being healthy (e.g. playing without being discriminated, being able to celebrate the next birthdays). The study concluded that the ongoing health education programs for children with HIV should incorporate the positive consequences of being healthy, instead of focusing heavily on medical-related topics. Having a positive outlook will hopefully motivate these children to adhere to their medications and therefore improve their quality of life.